Acetylcholine Upregulates Entamoeba histolytica Virulence Factors, Enhancing Parasite Pathogenicity in Experimental Liver Amebiasis - Medina-Rosales, Marina Nayeli; Muñoz-Ortega, Martín Humberto; García-Hernández, Mariana Haydee; Talamás-Rohana, Patricia; Medina-Ramírez, Iliana Ernestina; Salas-Morón, Larissa Guadalupe; Martínez-Hernández, Sandra Luz; Ávila-Blanco, Manuel Enrique; Medina-Rosales, Beatriz; Ventura-Juárez, Javier (Frontiers in Cellular and Infection Microbiology, 2021)
Abstract Entamoeba histolytica is an invasive enteric protozoan, whose infections are associated to high morbidity and mortality rates. However, only less than 10% of infected patients develop invasive amebiasis. The ability of E. histolytica to adapt to the intestinal microenvironment could be determinant in triggering pathogenic behavior. Indeed, during chronic inflammation, the vagus nerve limits the immune response through the anti-inflammatory reflex, which includes acetylcholine (ACh) as one of the predominant neurotransmitters at the infection site. Consequently, the response of E. histolytica trophozoites to ACh could be implicated in the establishment of invasive disease. The aim of this study was to evaluate the effect of ACh on E. histolytica virulence. Methods include binding detection of ACh to plasma membrane, quantification of the relative expression of virulence factors by RT-PCR and western blot, evaluation of the effect of ACh in different cellular processes related to E. histolytica pathogenesis, and assessment of the capability of E. histolytica to migrate and form hepatic abscesses in hamsters. Results demonstrated that E. histolytica trophozoites bind ACh on their membrane and show a clear increase of the expression of virulence factors, that were upregulated upon stimulation with the neurotransmitter. ACh treatment increased the expression of L220, Gal/GalNAc lectin heavy subunit (170 kDa), amebapore C, cysteine proteinase 2 (ehcp-a2), and cysteine proteinase 5 (ehcp-a5). Moreover, erythrophagocytosis, cytotoxicity, and actin cytoskeleton remodeling were augmented after ACh treatment. Likewise, by assessing the formation of amebic liver abscess, we found that stimulated trophozoites to develop greater hamster hepatic lesions with multiple granulomas. In conclusion, ACh enhanced parasite pathogenicity by upregulating diverse virulence factors, thereby contributing to disease severity, and could be linked to the establishment of invasive amebiasis.